Free, fair, and alive : the insurgent power of the commons - Bollier, David; Helfrich, Silke (New Society Publishers, 2019)
"Free, Fair, and Alive is a penetrating cultural critique, table-pounding political treatise, and practical playbook for "commoning"--Free, self-organizing systems ranging from alternative currencies to open-source everything. It presents a bold and compelling alternative to the dead-end, predatory market-state system."--